PENGARUH PROFITABILITAS, TUNNELING INCENTIVE, DAN INTANGIBLE ASSETS TERHADAP TRANSFER PRICING - Puspita Sari, Dwi; Purwaningsih, Sri (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
One of the problems faced by multinational companies occurs when determining transfer pricing, many different factors can affect the determination of transfer pricing. This study aims to determine the effect of profitability, tunneling incentives and intangible assets on transfer pricing. The population in this study are energy sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. As a research sample, 15 of 79 companies in the energy sector were taken using a purposive sampling method so that the total observations in this study were 75 observations. The data analysis technique used is multiple linear regression testing using SPSS version 25 software. The result of the analysis in this research showed that profitability and tunneling incentive has negative effect on transfer pricing whilet intangible assets positive effect on transfer pricing. In the determination coefficient test, it shows that profitability, tunneling incentive, and intangible assets variables affect transfer pricing by 34.4%, while the remaining 65.6% is explained by other variables outside of the study